Serum amyloid beta 42 levels correlated with metabolic syndrome and its components - Li, Kecheng; Zhou, Xiaoli; Liu, Youren; Li, Dongyu; Li, Yinyin; Zhang, Ting; Fu, Chunyan; Li, Lin; Hu, Yang; Jiang, Li (Frontiers in Endocrinology, 2024)
Beta amyloid accumulation in the brain appears to be a key initiating event in Alzheimer’s disease (AD) and factors associated with increased deposition of beta amyloid are of great interest. Enhanced deposition of amyloid-peptides is due to an imbalance between their production and elimination. Previous studies show that diminished levels of CSF amyloid beta 42 (A42) is a biomarker in AD;however, the role of serum A42 in AD is contradictory.BMI and obesity have been reported to be related to increased serum A42 levels.Therefore, we aimed to investigate the relation between metabolic syndrome (MetS), its clinical measures (abdominal obesity,high glucose,high triglyceride,low high-density lipoprotein cholesterol level,and hypertension),and serum A42 levels.A total of 1261 subjects,aged 18-89 years in Chengdu,China were enrolled from January 2020 to January 2021 to explore the correlation of serum A42 levels with body-mass index (BMI),blood lipids,and blood pressure.Further,as the risk of MetS is closely related to age,1212 participants (N = 49 with age >= 80-year-old were excluded) were analyzed for the correlation of serum A42 level and MetS clinical measures.The results showed that log-transformed serum A42 level was positively correlated with BMI (R = 0.29, P < 0.001), log-transformed triglyceride (R = 0.14, P < 0.001),and diastolic blood pressure (DBP) (R = 0.12, P < 0.001),and negatively correlated with high-density lipoprotein (HDL-c) (R = -0.18, P < 0.001).After adjusting for age, sex and other covariates, elevated serum A42 level was correlated with higher values of BMI (model1 = 2.694, model2 = 2.703) and DBP (model1 = 0.541, model2 = 0.546),but lower level of HDL-c (model2 = -1.741). Furthermore, serum A42 level was positively correlated with MetS and its clinical measures including BMI, DBP, and negatively correlated with HDL-c level in the Han Chinese population. However, the level of serum A42 did not show significant correlation with high glucose,and high triglyceride. These observations indicate that MetS and its components are associated with higher levels of serum A42 and hence limit the potential of serum A42 as a suitable diagnostic biomarker for AD. As such, we recommend serum A42 serve as a direct risk biomarker for MetS rather than for AD.